Novel phytoceramides containing fatty acids of diverse chain lengths are better than a single C18-ceramide N-stearoyl phytosphingosine to improve the physiological properties of human stratum corneum - Oh MJ; Cho YH; Cha SY; Lee EO; Kim JW; Kim SK; Park CS (Dove Medical Press, 2017)
Myoung Jin Oh,1 Young Hoon Cho,1 So Yoon Cha,1 Eun Ok Lee,2 Jin Wook Kim,2 Sun Ki Kim,2 Chang Seo Park1 1Department of Chemical and Biochemical Engineering, Dongguk University, Chung-gu, Seoul, 2LCS Biotech, Gwonseon-gu, Suwon-si, Gyeonggi-do, Republic of Korea Abstract: Ceramides in the human stratum corneum (SC) are a mixture of diverse N-acylated fatty acids (FAs) with different chain lengths. C24 is the major class of FAs of ceramides. However, there are also other classes of ceramides with diverse chain lengths of FAs, and these lengths generally range from C16 to C26. This study aimed to prepare several types of phytoceramide containing diverse chain lengths of N-acylated FAs and compare them with C18-ceramide N-stearoyl phytosphingosine (NP) in terms of their effects on the physiological properties of the SC. We chose natural oils, such as horse fat oil, shea butter, sunflower oil, and a mixture of macadamia nut, shea butter, moringa, and meadowfoam seed oil, as sources of FAs and phytosphingosine as a sphingoid backbone to synthesize diverse phytoceramides. Each phytoceramide exhibited a distinctive formation of the lamellar structure, and their FA profiles were similar to those of their respective natural oil. The skin barrier properties, as analyzed in human skin, clearly demonstrated that all the phytoceramides improved the recovery rate of the damaged SC and enhanced hydration better than C18-ceramide NP did. In conclusion, natural oil-derived phytoceramides could represent a novel class of ceramides for cosmetic applications in the development of an ideal skin barrier moisturizer. Keywords: fatty acid, chain length, phytoceramide, skin barrier, natural oil